Study of the Effect of the Behavior of Reinforced Beams Containing Small Openings - Hasanain S. Al Tamemi (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Openings in reinforced concrete beams can substantially impair structural behavior, particularly when located within the shear span. This study investigates the effectiveness of ferrocement strengthening, comprising a thin cement-mortar layer reinforced with welded wire mesh, in improving the behavior of reinforced concrete beams containing openings. A numerical finite element analysis was conducted using ABAQUS on seven reinforced concrete beams with square openings of varying dimensions relative to the beam depth. The numerical model was calibrated and validated against available experimental studies. Nonlinear static analysis was then performed to evaluate the beams’ maximum midspan displacement and maximum shear stress. The findings demonstrate that ferrocement-strengthened beams exhibited lower midspan displacement than their unstrengthened counterparts. The strengthening layer also substantially enhanced the beams’ resistance to maximum shear stress, resulting in improved overall structural behavior. These findings indicate that ferrocement strengthening is an effective method for mitigating the adverse effects of shear-span openings on reinforced concrete beams. The study contributes numerical evidence supporting the application of welded-wire-mesh ferrocement layers as a strengthening technique for reinforced concrete beams containing openings.